Successful treatment of Giant keloid on the right toes using trepanation combined with superficial radiotherapy (SRT-100): a case report with literature review - Song, Ying-hua; Zhu, Hui-min; Chen, Dan; Qu, Zi-lu; Zhang, Liang; Wei, Li (Frontiers in Medicine, 2024)
In dermatology, a keloid is one of the most common skin morphological abnormalities caused by excessive proliferation of fibroblasts. Keloids that are large or occur near important joint sites often cause varying degrees of physiological dysfunction in patients, therefore requiring medical treatment. A boy with congenital syndactyly developed huge keloids at the surgical site after undergoing surgical correction treatment. After treatment using trepanation combined with superficial radiotherapy (SRT-100) in our hospital, most of the boy’s keloids shrank and flattened. The affected foot returned to its normal appearance, and the boy could wear shoes normally. The boy did not complain of pain, numbness, or any other distinctive discomfort after completing the treatment. This suggested that the combination of trepanation and SRT-100 may be one of the options for treating hypertrophic keloids that cannot be treated by surgical excision.